Neutrophil extracellular traps in central nervous system disorders: mechanisms, implications, and emerging perspective - Qiao, Shan; Yuan, Jing; Zhang, Shan-chao; Lu, Ying-ying; Zhou, Peng; Xin, Tao (Frontiers in Immunology, 2025)
Neutrophil Extracellular Traps (NETs), as a crucial defense mechanism of neutrophils, have garnered increasing attention in recent years for their roles in central nervous system (CNS) disorders. This review comprehensively summarizes the fundamental characteristics and formation mechanisms of NETs, while highlighting the latest research advances regarding their involvement in various CNS diseases. Specific mechanistic insights are discussed, including how NETs exacerbate ischemic stroke through immunothrombosis, promote blood-brain barrier disruption in multiple sclerosis, and contribute to neuroinflammation in Alzheimer’s disease. The paper systematically explores the potential mechanistic contributions of NETs to disease pathogenesis and progression, as well as their prospects as diagnostic biomarkers and therapeutic targets. Through an in-depth analysis of the multifaceted roles of NETs in CNS pathologies, this review aims to provide novel insights and references for advancing the understanding, clinical diagnosis, and therapeutic management of central nervous system disorders.